Performance And Properties Of Polypropylene-Cellulose And Polypropylene- Oil Palm Empty Fruit Bunch Biocomposites - Mohd Khalid, Mohd Khalid (2007)
Natural fibers such as oil palm empty fruit bunch fibers (EFBF) can be used as environmentally friendly alternatives to conventional reinforcing fibers (e.g., glass) in composites. The interest in natural fiber-reinforced polymer composites is growing rapidly due to its high performance in terms of mechanical properties, significant processing advantages, excellent chemical resistance, low cost and low density. These advantages place natural fiber composites among the high performance composites having economic and environmental advantages. On the other hand, lack of good interfacial adhesion and poor resistance to moisture absorption make the use of natural fiber-reinforced composites less attractive. In order to improve their interfacial properties, these EFB fibers were subjected to chemical treatments, namely, chlorination, mercerization and acetylation. Preparation of cellulose by selective removal of non-cellulosic compounds constitutes the main objective of the chemical treatments of EFBF to improve the performance of fiber-reinforced composites. The objective of this study was to determine the effects of cellulose on the performance of the cellulose-reinforced biocomposites and comparing its property with the EFBF-reinforced biocomposites. Biocomposites were prepared by blending polypropylene-cellulose and polypropylene-EFBF at different weight ratios using a twin screw brabender. Further, effects of two different coupling agents namely MAPP and TMPTA on the properties of PP-cellulose and PP-EFBF biocomposite were also studied. These coupling agent were incorporated in order to enhance the fiber matrix adhesion. Mechanical and physical properties of both the biocomposites were evaluated. Compared to PP-EFBF biocomposites, PP-cellulose biocomposites showed better fiber-matrix interaction as observed from the good dispersion of fibers in the matrix system. The tensile fracture and impact fracture surfaces of the composites were characterized by scanning electron microscopy confirms the cellulose and PP interface had improved interfacial bonding. Incorporation of MAPP as coupling agent does not show significant improvement in case of PP-cellulose biocomposite. However, it showed good results for PP-EFBF biocomposite. On the other hand TMPTA coupled PP-cellulose biocomposite offered superior physical and mechanical properties. The strong intermolecular cellulose-matrix bonding indicates a decrease in the high rate of water absorption in PP-cellulose biocomposites. The dynamic mechanical analysis (DMA) and Thermogravimetry analysis (TGA) technique were also used to measure the viscoelastic properties and melting point of both the biocomposite. The scanning electron microscopy photographs of fiber surface characteristics and fracture surfaces of composites clearly indicated the extent of fiber-matrix interface adhesion